Finite element modeling of residual stress distribution in solid hardened cylindrical samples and samples with semicircular notch - Mikhail N Saushkin; Alexey Yu Kurov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2011)
We give a method for solving the problem of the distribution of residual stresses in a continuous surface hardened cylindrical samples and samples with a semicircular notch based on the ﬁnite element method. As the initial information the experimentally determined alone and / or two components of residual stresses in a hardened layer is used. By the example of a cylindrical specimen made of St. 45 and D16T steels the results of calculations performed by the proposed method are compared with the experimental data and the results of calculations by other methods.